Characteristics of childhood vitiligo and the progress of its treatment - Xiuzhen LI; Xiulian XU (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Vitiligo is a common depigmentation disease. Childhood vitiligo exhibits some characteristics in epidemiology, clinical manifestations, comorbidities, etc. In addition, considering the unique features of children's growth and development stages, the therapeutic approaches for pediatric vitiligo are different from those for adults. Although traditional therapy is still the main treatment for childhood vitiligo, glucocorticoids, calcipotriol and other conventional methods have limited efficacy. Hence, new therapies, including Janus kinase inhibitor, afamelanotide and prostaglandin analogues, are introduced in the treatment of vitiligo and are expected to be applied to children. Therefore, this article summarizes the characteristics, domestic and foreign guidelines, clinical trials and the latest research progress in the treatment of childhood vitiligo.